Analisis usaha mikro kecil dan menengah (UMKM) pada pondok pesentren di Kota Jambi - Avrizal, Avrizal; Haryadi, Haryadi; Hidayat, Syurya (Jurnal Paradigma Ekonomika, 2021)
This study aims to find out how the socioeconomic characteristics of MSMEs in Islamic boarding schools and what factors affect MSME income and what strategies to develop MSMEs at Islamic boarding schools. This research uses qualitative and quantitative approaches. The data used are primary data, a sample of 73 respondents. The respondents consisted of SMEs who were in the boarding school environment. Data collection was carried out through surveys and interviews using a questionnaire that was distributed to respondents. Data were analyzed using multiple regression analysis (multiple regression). The results showed that the variable fixed capital, operational capital and working hours significantly influence the income of UMKM traders in pesentren while the length of business and location variables did not significantly influence the income of UMKM traders in pondok pesentren. Â